Pembelajaran Memproduksi Teks Deskripsi dengan Model Show Not Tell di SMP - Winata, Nana Triana; Nasihin, Agus (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2022)
Writing is a skill that must be mastered through a long process. It needs presence, knowledge, time, and experience. In this activity, students were expected the capability to compose descriptive text. This research aimed to know and describe the students' writing ability taught using Show Not Tell Model and its effectiveness. The method used was quasi-experiment. Design research used that was nonequivalent control group design. The population in the research was the whole student class VII SMPN 1 Balongan Indramayu lesson years 2022/2023 while sampling only two classes, that was class VII B with 30 students and class VII D with 30 students. The technique interpretation sample conducted was technique sampling purposive. The instrument of this study was a test in the form of a test description—preparation of data conducted with a formula t-test. Based on the finding, the result of students' writing ability in composing descriptive text through Show Not Tell Model increased, as proved by the average score of 85.50. Statistically, it was proved by the Tcounted= 6.44 and Ttable=1.70. Moreover, the significant value shows that it is not greater than 0.05. Hence, it could be summed up that Show Not Tell Model effectively increases students' writing ability in composing descriptive text